Water loss from Leogryllus bimaculatus Saussure treated with certain insecticides and under certain other experimental environmental conditions (Saltatoria: Gryllidae). - Srivastava, R. P. (Contributions to Entomology = Beiträge zur Entomologie, 1969)
These investigations reveal that water conservation in Leogryllus bimaculatus Saussure is affected both by the limited openings of the spiracles and the impermeable nature of the cuticle. If any of these mechanisms is disturbed, considerable water loss may occur. The investigations also show great water loss from the insect following treatment with a number of insecticides.